More Giving or More Givers? The Effects of Tax Incentives on Charitable Donations in the UK - Miguel Almunia; Irem Guceri; Ben Lockwood; Kimberley Ann Scharf; Benjamin Lockwood (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper estimates the effects of tax incentives on charitable contributions in the UK, using the universe of self-assessment income tax returns between 2005 and 2013. We exploit variation from a large reform in 2010 to estimate intensive and extensive-margin tax-price elasticities of giving. Using a predicted-tax-rate instrument for the price of giving relative to consumption, we find an intensive-margin elasticity of about -0.2 and an extensive-margin elasticity of -0.1, yielding a total elasticity of about -0.3. To further explore the extensive-margin response, we propose a model with a fixed cost of declaring donations and obtain a structural estimate of that cost of around 47. We also study the welfare effects of tax incentives, extending the theoretical literature to allow for extensive-margin giving and for a fixed cost of declaring donations. Taking into account these factors, there is a case for increasing the subsidy on charitable giving in the UK.
Keywords: H24; H31; D64; 330; charitable giving; tax incentives; welfare